Violação de direitos e medidas protetivas na concepção de juízes que atuam em Juizados de Infância e Juventude - Lindinger, Luciana (2014)
The present dissertation was developed through an exploratory study and it has as its theme the violation of children and adolescents’ rights. The focus was the analysis of conceptions of the judges who work in Childhood and Youth Courts and deal constantly with situations that demands their attitude towards cases in which protective measures are required. Participants were six law judges from Childhood and Youth Courts (CYC), all of them work at Espírito Santo. In order to understand the presented phenomenon it was considered that the violation of the children and adolescents’ rights is a multidetermined event, and because of it is was taken into consideration the historical process of the constitution of the family and childhood, both being understood as social institutions, as well as the conception of vulnerability and social risk. The data was obtained through interviews and its interpretation and systematization was based on two different procedures: the Content Analysis (CA) and the Alceste software. By means of the results it was possible to observe a number of conceptions the judges have in relation to the ambit they work on, namely: they believe the that they have a profile that differs from the other judges, although they all got to work at such courts for professional chance; they admit that their values and experiences complement their legal knowledge in order to guide their comprehension towards the phenomena they have to decide about; they recognize the importance of other professionals collaboration in a way that make them more convicted about the situations they have to evaluate; they understand that the sentence execution convene different institutions and professionals to articulate themselves , mainly in the socio-legal assistance network system; they consider that the vulnerability and risk aspects in which child and the adolescent are susceptible to, come from associated factors that their legal representatives are also susceptible, and it indicates the importance of the implementation of family oriented public policies; and, finally, they point out that apart from the family itself, the state also violates the rights of children and adolescents, given the fact that public policies that promotes mechanisms to guarantee personal and social constitutional rights are not properly developed.